Ultraviolet‐Durable Flexible Nonfullerene Organic Solar Cells Realized by a Hybrid Nanostructured Transparent Electrode. Issue 5 (30th January 2020) - Xu, Tao; Gong, Chunliu; Wang, Shuanglong; Lian, Hong; Lan, Weixia; Lévêque, Gaëtan; Grandidier, Bruno; Plain, Jerôme; Bachelot, Renaud; Wei, Bin; Zhu, Furong
Abstract : A significant enhancement in ultraviolet (UV)‐durable indium tin oxide (ITO)‐free flexible nonfullerene organic solar cells (OSCs) is demonstrated using a hybrid nanostructured flexible transparent electrode (FTE), comprising a mixture of 0D silver nanoparticles, 1D Ag nanowires, and 2D exfoliated graphene sheets. The FTE exhibits high optical transparency and electric conductivity, good air stability, and full solution fabrication capability at a low processing temperature. An average power convention efficiency of 8.15% is obtained for the flexible nonfullerene OSCs, based on the blend of poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐ b :4, 5‐ b ′]dithiophene))‐alt‐(5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐ c :4′, 5′‐ c ′]dithiophene‐4, 8‐dione)] (PBDB‐T): 3, 9‐ bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐ d :2′, 3′‐ d ′]‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′] dithiophene (ITIC). The flexible PBDB‐T:ITIC OSCs exhibit an excellent UV durability compared with the ITO‐based control cell, realized by incorporating an FTE with a tailored absorption at wavelengths <380 nm. The novel FTE developed in this work provides a promising alternative to ITO for use in UV‐durable flexible OSCs, serving as a built‐in UV filter to impede an inevitable UV‐induced degradation in ITO‐based OSCs. Abstract : An ultraviolet‐durable indium tin oxide‐free flexible nonfullerene organic solar cell is demonstrated, realized by incorporating a hybrid nanostructured flexible transparent electrode with a tailored absorption at wavelengths <380 nm.